Factors affecting photovoltaic solar technology usage intention among households in Malaysia: Model integration and empirical validation - Alam, S.S. (MDPI AG, 2021)
The objective of this research is to identify the antecedents affecting the behavioural intentions of local housing residences in using photovoltaic (PV) solar technology in their houses. An integrated model of behavioural intention to use PV solar technology is tested in this research. This study combined the theory of reason action (TRA), technology acceptance model (TAM), theory of planned behaviour (TPB) and diffusion of innovation (DOI) theory. Additional factors, including cost, awareness, and government initiatives, are also included in this model. The proposed model findings are based on empirical data from a sample of 382 residences in Malaysia. This study postulates that the intent to use PV solar technology is predicted by trialability, compatibility, perceived ease of use, relative advantage, observability, perceived behavioural control, attitude, subjective norms, cost, government initiatives, and level of awareness towards photovoltaic technology. The integrated model achieves 54 variance explained for usage intention of PV solar technology among housing residences in Malaysia. The findings suggest an integrated model for the acceptance intention of PV solar technology, which can assist stakeholders in planning, evaluating, and executing PV solar technology. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.